Pemanfaatan Puree Labu Kuning dalam Pembuatan Flakes - Thoriq Afif Ramadhan; Niken Purwidiani; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (Student Scientific Creativity Journal, 2023)
Pumpkin cereal flakes are cereal in the form of flakes made from pumpkin puree, tapioca flour, sugar and salt. This study aims to determine: 1) the best formula for pumpkin flakes cereal; 2) organoleptic properties of pumpkin flakes cereal which include texture, shape, taste, aroma, color, and level of preference; 3) nutritional content of pumpkin flakes cereal which includes Vitamin A and Test Proximate (water, fat, carbohydrates, protein, and ash); and 4) selling price of pumpkin flakes in packs weighing 34 grams/package. This trial was conducted with three trials to find out the best pumpkin cereal formula that met the criteria. Based on the engineering results for making pumpkin flakes, 1) the formula for chayote squash consists of 100% pumpkin puree, 43% tapioca flour, 3.5% granulated sugar, and 2.5% salt. 2) Pumpkin cereal flakes are brownish yellow in color, have the shape of round flat flakes with intact edges, have a distinctive pumpkin aroma, taste slightly sweet and have a savory taste typical of pumpkin, have a crunchy texture and are well liked by all panelists. 2) The nutritional content of pumpkin flakes per 100 grams contains 102.50 mg of vitamin A, 0.21% water content, 6.79% protein content, 3.04% fat content, 87.93% carbohydrates, and an ash content of 1.36%. 3) The selling price of pumpkin tofu cereal is IDR 6,950 per pack weighing 34 grams.